Can Well-Being, Positive Affect, or Contact with the Elderly Be Potential Predictors of Attitudes towards Older People? A Study on the Polish Population. (18th November 2022) - Marta, Podhorecka; Jakub, Husejko; Anna, Pyszora; Kornelia, Kędziora-Kornatowska; Agnieszka, Woźniewicz
Abstract : Objectives . The age discrimination, i.e., ageism, is still a current social problem. Therefore, it is justified to conduct studies increasing the knowledge about this phenomenon. The aim of our research was to determine whether the type of personality, manifested mood, and well-being can influence the attitudes towards the elderly. Material and Methods . During the research, we collected information from 923 participants and we used the following tools: demographic questionnaire, Kogan's Attitudes Toward Old People Scale, Euthymia Scale, WHO-5 Well-Being Index, and the author's questionnaire on contacts with an elderly person. Results . We used R 4.0.2 to analyse the data. In our current model study, we did not observe statistically significant relationships between the WHO-5 or ES scores and the KOAP score. Conclusions . The conducted study did not show any correlation between mood, sense of well-being, or contact with the elderly and attitude towards the elderly. The results of our study may become the basis for further research to find the relationship between the mood and well-being shown in attitudes towards the elderly. Perhaps, however, the assumption should also be made that there is no such relationship.